2023
DOI: 10.3390/bdcc7030147
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Robotic Technologies and Artificial Intelligence in Pharmacy and Medicine: Paving the Way for the Future of Health Care—A Review

Maryna Stasevych,
Viktor Zvarych

Abstract: The future of innovative robotic technologies and artificial intelligence (AI) in pharmacy and medicine is promising, with the potential to revolutionize various aspects of health care. These advances aim to increase efficiency, improve patient outcomes, and reduce costs while addressing pressing challenges such as personalized medicine and the need for more effective therapies. This review examines the major advances in robotics and AI in the pharmaceutical and medical fields, analyzing the advantages, obstac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 138 publications
0
7
0
Order By: Relevance
“…Artificial intelligence technologies, including machine learning algorithms, are increasingly being used in that regard hence physicians who actively use artificial intelligence tools in their clinical practice will likely have a deeper understanding of artificial intelligence (Basu et al, 2020). Similarly, a higher mean knowledge score by pharmacists could be due to a progressive increase in the use of artificial intelligence innovations for drug design and development in the pharmaceutical sector (Raza et al, 2022;Stasevych and Zvarych, 2023). These novel findings clearly identify potential early adopters of the technology, and this can be useful in policy articulation and implementation planning.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence technologies, including machine learning algorithms, are increasingly being used in that regard hence physicians who actively use artificial intelligence tools in their clinical practice will likely have a deeper understanding of artificial intelligence (Basu et al, 2020). Similarly, a higher mean knowledge score by pharmacists could be due to a progressive increase in the use of artificial intelligence innovations for drug design and development in the pharmaceutical sector (Raza et al, 2022;Stasevych and Zvarych, 2023). These novel findings clearly identify potential early adopters of the technology, and this can be useful in policy articulation and implementation planning.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that a lack of training can hinder AI adoption in healthcare, and healthcare professionals should be equipped with the necessary knowledge and skills to effectively utilize AI tools ( Choudhury & Asan, 2022 ). The idea of a proactive approach in preparing the workforce for AI-driven changes aligns with the broader notion that embracing innovation and staying ahead of technological advancements is essential for the future of healthcare ( Stasevych & Zvarych, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The future of robotics in pharmacy is very engaging. Routine tasks are automated by AI and robotics, which improves patient care and lowers costs while increasing the efficiency of healthcare delivery [3]. Further, another field where technologies are having a big impact is pharmacy robotic process automation (RPA).…”
Section: Literature Review 13 Robotic Pharmacy and Augmenting Service...mentioning
confidence: 99%